Psychological Condition of Richard Strickland in The Shape of Water - Alberta Natasia Adji; Azis Bilbargoya (Balai Bahasa Provinsi Riau, 2018)
This study strives to elucidate the psychological condition of Richard Strickland, the main antagonist in Guillermo Del Toro’s and Daniel Kraus’ novel The Shape of Water. This study uses the close-reading method and Sigmund Freud’s psychoanalysis in examining the psychological factors which trigger the three distinctive features of Richard Strickland, namely hate, disgust, and fear, that lead him to pick up destructive murderous habits. The results of data analysis indicate that (1) Strickland’s fear of intimacy has made him distant from his family and colleagues, preventing him from understanding them and instead triggering him to be too attached to General Hoyt’s influence, (2) Strickland’s low self-esteem has made him powerless to defy Hoyt’s authorities but made him feel justified to perform displacement, by torturing and harrassing “lesser” people and animals, and (3) Strickland’s unstable sense of self, rooted on his guilt of conducting violence, making him repress his psychological wounds and destroying his own life.